Dimerisation increases the immunogenicity of recombinant Parj1/Parj2 allergens. (March 2015) - Barletta, B; Butteroni, C; Bonura, A; Bondi, ML; Colombo, P; Di Felice, G
Purified recombinant Parj1 and Parj2 allergens bind an IgE repertoire common to the Parietaria species, allowing their use as marker molecules for diagnosis and therapy of allergic disease induced by the Urticaceae family. Preclinical studies on the in vivo immunogenicity of recombinant Parj1, Parj2 and their isoforms indicated differential capacity to induce IgG1 antibody responses, as indication of potential clinical use. A recombinant hetero-dimeric hybrid derivative (PjED), encompassing the shorter Parj1 isoform (Parj1.0201) and Parj2 allergen, was characterised. In vivo immunisation with PjED induces IgG1 antibodies capable of binding all the isoforms of Parietaria major allergens, overcoming the poor immunogenicity of single monomeric allergens. This feature makes PjED a promising candidate molecule to be further characterised for clinical applications in the treatment of Parietaria allergy.